QoE Analysis of Open Access Network at the University of Riau - Anhar, Anhar; Putri, Sonia Maharani (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
This journal outlines a QoE network analysis conducted through both subjective and objective methods. The subjective approach involved the distribution of questionnaires via Google Forms to Riau University students using open access network, while the objective method utilized open access network in the Engineering Faculty Lobby and the Riau University Library, facilitated by the Google LightHouse tool. This analysis extended over a span of five days, encompassing morning, afternoon, and evening measurements, focusing on five web-based applications: YouTube, Facebook, WhatsApp, Instagram, and the Riau University Portal. The parameters assessed included Performance, Accessibility, Best Practices, and SEO. The QoE measurement results were presented in both tabular and graphical formats. The subjective method yielded a MOS value of 3.45, classifying it as